Frame me if you must: PrEP framing and the impact on adherence to HIV Pre-exposure Prophylaxis. (4th October 2017) - Ellorin, Eric; Blumenthal, Jill; Jain, Sonia; Sun, Xiaoying; Corado, Katya; Dube, Michael; Moore, David; Morris, Sheldon; ,
Abstract: Background: "PrEP whore" has been used both as a pejorative by PrEP opponents in the gay community and, reactively, by PrEP advocates as a method to reclaim the label from stigmatization and "slut-shaming." The actual prevalence and impact of such PrEP-directed stigma on adherence have been insufficiently studied. Methods: CCTG 595 was a randomized controlled PrEP demonstration project in 398 HIV-uninfected MSM and transwomen. Intracellular tenofovir-diphosphate (TFV-DP) levels at weeks 12 and 48 were used as a continuous measure of adherence. At study visits, participants were asked to describe how they perceived others' reactions to them being on PrEP. These perceptions were categorized a priori as either "positively framed, " "negatively framed, " or both. We used Wilcoxon rank-sum to determine the association between positive and negative framing and TFV-DP levels at weeks 12 and 48. Results: By week 4, 29% of participants reported perceiving positive reactions from members of their social groups, 5% negative, and 6% both. Reporting decreased over 48 weeks, but positive reactions were consistently reported more than negative. At week 12, no differences in mean TFV-DP levels were observed in participants with positively-framed reactions compared with those reporting no outcome or only negatively-framed (1338 [IQR, 1036-1609] vs. 1281 [946-1489] fmol/punch, P = 0.17). Additionally, no differences were observed in those with negative reactions vs. those without (1209 [977–1427] vs. 1303 [964–1545], P = 0.58). At week 48, mean TFV-DP levels trended toward being higher among those that report any reaction, regardless if positive (1335 [909–1665] vs. 1179 [841–1455], P = 0.09) or negative (1377 [1054–1603] vs. 1192 [838–1486], P = 0.10) than those reporting no reaction. At week 48, 46% of participants reported experiencing some form of PrEP-directed judgment, 23% reported being called "PrEP whore, " and 21% avoiding disclosing PrEP use. Conclusion: Over 48 weeks, nearly half of participants reported some form of judgment or stigmatization as a consequence of PrEP use. However, individuals more frequently perceived positively framed reactions to being on PrEP than negative. Importantly, long-term PrEP adherence does not appear to suffer as a result of negative PrEP framing. Disclosures: All authors: No reported disclosures.